Carbon fiber composite insulating, heat-conducting and wave-absorbing gasket as well as preparation method and application thereof
By using high-temperature sintered carbonized polyimide film in the thermal wave-absorbing gasket to form a carbon fiber gel sheet, and by multiple impregnation and cross-linking and curing filler to form a carbon fiber cloth with excellent thermal conductivity, the problem of insufficient thermal conductivity and insulation performance of the existing thermal wave-absorbing gasket is solved, and excellent thermal conductivity in horizontal and vertical directions is achieved.
Patent Information
- Application Number
- CN202411594653.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-03-14
AI Technical Summary
During the processing process, existing thermal wave-conducting and wave absorption gaskets have problems such as uneven wave absorption, easy leakage current, poor thermal conductivity and thermal conduction anisotropy of the carbon fiber layer, making it difficult to improve thermal conductivity and insulation performance at the same time.
By sintering and carbonizing the polyimide film at high temperature, a carbon fiber gel sheet with an internal space structure is formed, and through multiple impregnation and cross-linking curing, it is filled with thermally conductive fillers of different particle sizes to form a carbon fiber cloth with excellent thermal conductivity, and finally it is combined with the thermally conductive insulating layer.
It realizes excellent thermal conductivity of carbon fiber composite insulated heat-absorbing gasket in horizontal and vertical directions, improves flexibility, thermal conductivity and insulation performance, and solves the problem of insufficient thermal conductivity and insulation performance of existing products.
Smart Images

Figure CN119615607A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat-conducting and wave-absorbing gaskets, and in particular to a carbon fiber composite insulating heat-conducting and wave-absorbing gasket and a preparation method and application thereof. Background Art
[0002] The thermally conductive and absorbing silicone pads currently on the market are mainly made of alumina ceramics as thermal conductive fillers, ferrite as absorbing fillers and silicone oil, which are further cross-linked to form a soft silicone gasket. In order to ensure the softness of the silicone gasket and improve the insulation performance at the same time, the common practice in the prior art is to use ferrite as the absorbing gasket layer and conventional alumina ceramics as the thermal conductive layer through coating technology to make a composite, with the absorbing gasket layer in the middle and conventional thermal conductive insulation layers on both sides. This solution has the following disadvantages:
[0003] 1. Due to processing limitations, the finished thin film absorbs waves unevenly and is prone to current leakage.
[0004] 2. It is difficult to modify the absorbing filler, the filling amount is small, and the thermal conductivity is poor. It is difficult to improve the thermal conductivity under the same absorbing effect.
[0005] 3. Use ferrite, which has a high density.
[0006] In addition, simply using carbon fiber layers for composites has poor strength and because of the anisotropy of thermal conductivity of the carbon fiber layer (it conducts electricity or heat only in one direction, but has high resistance or almost no electricity or heat conduction in other directions), it causes obstruction in the vertical heat conduction direction, which does not meet the thermal conduction design as a thermal conductive interface material.
[0007] Therefore, new technologies are urgently needed to improve the thermal conductivity and insulation properties of existing composite insulating thermally conductive absorbing gaskets. Summary of the invention
[0008] The purpose of the present invention is to provide a carbon fiber composite insulating heat-conducting wave-absorbing gasket and its preparation method and application to solve the above technical problems. The preferred technical solutions among the many technical solutions provided by the present invention can produce many technical effects as described below.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] A method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket comprises the following steps:
[0011] The polyimide film of a specified thickness is sintered and carbonized at a high temperature to form a carbon fiber gel sheet with an internal space structure;
[0012] The carbon fiber gel sheet is immersed in an impregnation slurry prepared by a first thermally conductive filler, and then the slurry is cross-linked and cured. After the cross-linking and curing, the carbon fiber gel sheet is immersed in an impregnation slurry prepared by a second thermally conductive filler, and then the slurry is cross-linked and cured to obtain a carbon fiber cloth filled with thermally conductive fillers of different particle sizes in the internal space structure; wherein the particle size of the first thermally conductive filler is larger than the particle size of the second thermally conductive filler, and the particle size of the first thermally conductive filler and the particle size of the second thermally conductive filler are both not less than 0.5 μm and not more than 5 μm;
[0013] Aluminum oxide and aluminum nitride are mixed in a certain proportion to form a thermally conductive and insulating ingredient, and components including vinyl silicone oil, thermally conductive and insulating ingredients, and additives are mixed in parts by weight to form a slurry with thermally conductive and insulating properties;
[0014] The mixed slurry is compounded on one side or both sides of the carbon fiber cloth and heated and cured to obtain a carbon fiber composite insulating heat-conducting wave-absorbing gasket.
[0015] In some embodiments, the weight proportions of vinyl silicone oil, thermal conductive insulating ingredients, and additives are as follows:
[0016] 100 parts of vinyl silicone oil, 2000 parts of thermal conductive insulating ingredients, and 2 parts of additives.
[0017] In some embodiments, the viscosity of the vinyl silicone oil at 25° C. is in the range of 500 cp-2000 cp; the auxiliary agent is one or more of a Perkin catalyst, a cross-linking hydrogenated silicone oil, and a silane coupling agent.
[0018] In some embodiments, obtaining a carbon fiber cloth having thermal conductive fillers of different particle sizes filled in the internal space structure comprises the following steps:
[0019] The carbon fiber gel sheet is immersed in the impregnation slurry prepared by the first thermal conductive filler for impregnation, and after impregnation, it is calendered by a double comma roller and the surface is flattened, and after calendering and surface flattening, the slurry is cross-linked and cured, and after curing, the impregnation and curing steps are repeated several times to obtain a carbon fiber gel sheet filled with the first thermal conductive filler in the internal space structure;
[0020] The impregnated and cured carbon fiber gel sheet is immersed in the impregnation slurry prepared by the second thermally conductive filler for impregnation, and after impregnation, it is calendered by a double comma roller and the surface is flattened. After calendering and surface flattening, the slurry is cross-linked and cured. After curing, this step of impregnation and curing is repeated several times to obtain a carbon fiber cloth filled with the second thermally conductive filler in the gap formed between the first thermally conductive filler and the unfilled internal space structure.
[0021] In some embodiments, the impregnation slurry prepared from the first thermally conductive filler comprises the following steps:
[0022] Mix and disperse the following components by weight and dilute them into a slurry:
[0023] 100 parts of silicone oil, 500 parts of the first thermal conductive filler, 5 parts of auxiliary agent, and 250-280 parts of diluent;
[0024] The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent;
[0025] The first thermally conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride;
[0026] The dilution solvent is an alkane solvent;
[0027] The auxiliary agent is one or more of a Perkin catalyst, a hydrogen-containing silicone oil having a cross-linking effect, and a silane coupling agent.
[0028] In some embodiments, the silicone oil of the impregnation slurry prepared by the first thermally conductive filler is vinyl silicone resin, and its viscosity ranges from 100cp to 300cp at 25°C; the first thermally conductive filler is alumina, and its particle size distribution is: D50 equals 2μm, D100 is less than 3μm.
[0029] In some embodiments, the impregnation slurry prepared from the second thermally conductive filler comprises the following steps:
[0030] Mix and disperse the following components by weight and dilute them into a slurry:
[0031] 100 parts of silicone oil, 400-800 parts of the second thermal conductive filler, 5 parts of the auxiliary agent, and 250-280 parts of the diluent; wherein,
[0032] The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent;
[0033] The second thermally conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride;
[0034] The dilution solvent is an alkane solvent;
[0035] The auxiliary agent is one or more of a Perkin catalyst, a hydrogen-containing silicone oil having a cross-linking effect, and a silane coupling agent.
[0036] In some embodiments, the silicone oil of the impregnation slurry prepared by the second thermally conductive filler includes 20 parts of vinyl silicone resin and 80 parts of vinyl silicone oil; the viscosity of the vinyl silicone resin at 25° C. is equal to 100 cp, and the viscosity of the vinyl silicone oil at 25° C. is equal to 5000 cp;
[0037] The second thermally conductive filler includes 300-500 parts of aluminum oxide and 100-300 parts of aluminum nitride. The particle size D100 of the aluminum oxide is not less than 0.5 μm and not more than 1 μm, and the particle size D50 of the aluminum nitride is equal to 1 μm.
[0038] According to the overall inventive concept, the second aspect of the present invention further provides a carbon fiber composite insulating thermally conductive absorbing gasket, which is prepared by the preparation method described above, and includes an absorbing and thermally conductive layer composed of a carbon fiber cloth, and an insulating and thermally conductive layer composed of an insulating thermally conductive slurry covering one or both sides of the carbon fiber cloth; the thickness of the absorbing and thermally conductive layer is in the range of 0.05mm-0.5mm.
[0039] According to the overall inventive concept, the third aspect of the present invention further provides an application of the carbon fiber composite insulating heat-conducting and wave-absorbing gasket described above for insulation, heat conduction and wave absorption between components of a heat source and a heat sink.
[0040] Implementing one of the above technical solutions of the present invention has the following advantages or beneficial effects:
[0041] The present invention uses polyimide film as a raw material to make carbon fiber cloth, and uses the carbon fiber cloth as the absorbing layer of the gasket and has excellent thermal conductivity. The internal space of the carbon fiber gel formed after the polyimide film is carbonized is filled with thermal conductive fillers of different particle sizes in batches to obtain excellent thermal conductivity in the horizontal and vertical directions and to strengthen the carbon fiber layer. Then, a conventional thermal conductive silicone layer is composited on one or both sides to achieve good wave absorption, heat conduction, and insulation between components and radiators that serve as heat sources. The carbon fiber composite insulating thermal conductive absorbing gasket prepared by the present invention has excellent thermal conductivity in the horizontal and vertical directions, and its softness, thermal conductivity, and insulation properties are significantly improved compared to existing products. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. It is obvious that the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work. In the drawings:
[0043] Figure 1 This is a flow chart of a method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to an embodiment of the present invention;
[0044] Figure 2 The microscopic morphology of the carbon fiber gel sheet with anisotropic internal gap according to the embodiment of the present invention;
[0045] Figure 3It is a detailed flow chart of step S200 in the method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to an embodiment of the present invention;
[0046] Figure 4 is the microscopic morphology of the carbon fiber cloth prepared in the embodiment of the present invention;
[0047] Figure 5 It is a schematic diagram of heat conduction in horizontal and vertical directions of the carbon fiber cloth prepared in an embodiment of the present invention. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solutions and advantages of the present invention clearer, the various exemplary embodiments to be described below will refer to the corresponding drawings, which constitute a part of the exemplary embodiments, wherein various exemplary embodiments that may be used to implement the present invention are described. Unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementation methods described in the following exemplary embodiments do not represent all implementation methods consistent with the present disclosure. It should be understood that they are only examples of processes, methods, devices, etc. that are consistent with some aspects of the present disclosure as detailed in the attached claims, and other embodiments may also be used, or the embodiments listed herein may be modified in structure and function without departing from the scope and essence of the present invention.
[0049] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", etc. indicate the orientation or positional relationship based on the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the elements referred to must have a specific orientation, be constructed and operated in a specific orientation. The terms "first", "second", etc. are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. The term "multiple" means two or more. The terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, an integral connection, a mechanical connection, an electrical connection, a communication connection, a direct connection, an indirect connection through an intermediate medium, and can be the internal connection of two elements or the interaction relationship between two elements. The term "and / or" includes any and all combinations of one or more related listed items. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to the specific circumstances.
[0050] In order to illustrate the technical solution of the present invention, a specific embodiment is used below for description, and only the parts related to the embodiment of the present invention are shown.
[0051] Embodiment 1:
[0052] like Figure 1As shown, the present invention provides a method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket, comprising the following steps:
[0053] S100, sintering and carbonizing a polyimide film of a specified thickness at a high temperature to form a carbon fiber gel sheet with an internal space structure.
[0054] S200, immerse the carbon fiber gel sheet in an impregnation slurry prepared by the first thermally conductive filler, perform slurry cross-linking and curing on it after impregnation, immerse it in an impregnation slurry prepared by the second thermally conductive filler after cross-linking and curing, and perform slurry cross-linking and curing on it to obtain a carbon fiber cloth with thermally conductive fillers of different particle sizes filled in the internal space structure. Among them, the particle size of the first thermally conductive filler is larger than the particle size of the second thermally conductive filler, and the particle size of the first thermally conductive filler and the particle size of the second thermally conductive filler are not less than 0.5μm, and not more than 5μm. It should be noted that the particle size of the first thermally conductive filler and the second thermally conductive filler can be selected within the particle size range of 0.5-5μm of the thermally conductive filler, and this particle size range ensures that it is effectively filled into the internal space of the carbon fiber aerogel and achieves a better filling effect. It can be understood that slurry cross-linking and curing refers to the chemical cross-linking between vinyl and hydrogen bonds through Perkin's catalysis, including but not limited to heating, and the cross-linking curing temperature is 80℃-125℃;
[0055] S300, mixing aluminum oxide and aluminum nitride in a certain proportion to form a thermally conductive insulating ingredient, and mixing components including vinyl silicone oil, thermally conductive insulating ingredients, and additives in parts by weight to form a slurry with thermally conductive and insulating properties.
[0056] S400, compounding the mixed slurry on one side or both sides of the carbon fiber cloth and heating and curing it to obtain a carbon fiber composite insulating heat-conducting wave-absorbing gasket. The compounding method includes scraping, spraying or calendering.
[0057] The present invention uses polyimide (PI) film as a raw material to make carbon fiber cloth, and uses the carbon fiber cloth as the wave absorbing layer of the gasket and has excellent thermal conductivity. The internal space of the carbon fiber gel is filled with thermal conductive fillers of different particle sizes in stages to obtain excellent thermal conductivity in the horizontal and vertical directions and to strengthen the carbon fiber layer, and then a conventional thermal conductive silicone layer is composited on one side or both sides to achieve good wave absorption, thermal conductivity and insulation between components and heat sinks as heat sources.
[0058] It should be noted that the wave-absorbing performance of the carbon fiber cloth obtained after filling is determined by the physical properties of the carbon fiber cloth prepared as described above. According to the element classification of the wave-absorbing material, the carbon fiber cloth prepared in this embodiment is a carbon-based wave-absorbing material, which achieves efficient wave-absorbing performance through resistive loss related to conductivity.
[0059] It is understandable that the excellent absorbing ability of carbon fiber has the advantages of greater thermal conductivity and low density than the ferrite used in conventional silicon absorbing gaskets. The excellent horizontal conduction of carbon fiber does not need to be limited to local heat dissipation of heat source components, but can achieve full coverage heat dissipation of the product.
[0060] Furthermore, steps S100 to S200 are to obtain a carbon fiber layer with reliable heat conduction and wave absorption functions, thereby improving anisotropy and strengthening the carbon fiber layer structure, and obtaining a carbon fiber layer with excellent directional conduction performance (both horizontal and vertical directions have conduction performance), and the resistivity reaches the milliohm level. In step S100, the polyimide is heat-treated to volatilize all or most of the non-carbon components in the polymer, such as hydrogen, oxygen, nitrogen, etc., and the remaining part is mainly carbon, forming a polyimide carbonized film. The carbonization process is as follows:
[0061] 600℃: The radial arrangement of polyimide structure molecules is disrupted and gradually transforms into a crystalline structure.
[0062] 700℃: Carbonyl group breaks and deoxidizes.
[0063] 800℃: Hybridization occurs, residual nitrogen and oxygen are removed, and polycyclic compounds are formed.
[0064] 2300℃: The molecular structure of carbon changes significantly and begins to transform into a hexagonal layered graphite structure.
[0065] In some specific embodiments, the temperature range of high temperature sintering and carbonization is: 800°C-1000°C. In this embodiment, the polyimide film is sintered and carbonized at high temperature in a nitrogen atmosphere, and the carbonization temperature is stopped after reaching 1000°C. It should be noted that under conventional sintering technical conditions, high temperature carbon elements under oxygen conditions will burn to form carbon oxides, while the temperature for forming carbon-nitrogen bonding under a nitrogen atmosphere needs to be higher to form a protective effect and avoid the formation of carbon oxides.
[0066] like Figure 2 As shown, the present invention uses a chemically biaxially stretched polyimide film as a raw material for carbonization, and stops graphitization after the carbonization temperature reaches 1000°C in a nitrogen atmosphere, thereby obtaining a carbon fiber gel sheet with an internal gap (spatial structure) and anisotropy (anisotropy means that only one direction conducts) (see Figure 2 shown).
[0067] In some specific embodiments, the thickness of the polyimide film is in the range of 0.05 mm to 0.5 mm. It should be noted that the thickness of the polyimide film is mainly determined by the enhanced impregnation process of step S200 and the adjustment of the absorbing frequency band.
[0068] like Figure 3As shown, in some examples, the internal gaps of the prepared carbon fiber gel sheet are filled and strengthened by a thermally conductive silicone impregnation curing method. The impregnation material is a slurry in which silicone oil and thermally conductive filler are mixed and diluted with a solvent, and a high-strength and high-thermal-conductive fiber layer is obtained by impregnation coating. Specifically, the specific steps of step S200 include:
[0069] S210, immersing the carbon fiber gel sheet into the impregnation slurry prepared by the first thermally conductive filler, and after impregnation, calendering it with a double comma roller and smoothing the surface. After calendering and smoothing the surface, the slurry is cross-linked and cured. After curing, the impregnation and curing steps are repeated several times to obtain a carbon fiber gel sheet filled with the first thermally conductive filler in the internal space structure.
[0070] S220, immersing the impregnated and cured carbon fiber gel sheet into the impregnation slurry prepared by the second thermally conductive filler for impregnation, and after impregnation, calendering with a double comma roller and smoothing the surface, and after calendering and smoothing the surface, cross-linking and curing the slurry, and repeating this step of impregnation and curing several times after curing to obtain a carbon fiber cloth filled with the second thermally conductive filler in the gap formed between the first thermally conductive filler and the unfilled internal space structure.
[0071] It should be emphasized that the particle size of the first thermally conductive filler is larger than that of the second thermally conductive filler. By filling the internal space structure of the carbon fiber gel sheet with a thermally conductive filler of large particle size, and filling the gap between the thermally conductive filler of large particle size and the unfilled internal space structure with a thermally conductive filler of small particle size, the carbon fiber cloth is in the form of large particles (first thermally conductive filler) bonded to the carbon fiber, and small particles (second thermally conductive filler) further fill the remaining gaps between the large particles and the carbon fiber to form a pile. This enables the carbon fiber cloth to achieve thermal conductivity in both horizontal and vertical directions.
[0072] In some specific embodiments, the impregnation slurry prepared from the first thermally conductive filler comprises the following steps:
[0073] The following components in parts by weight are mixed and dispersed, and then diluted with isoparaffin to form a slurry:
[0074] 100 parts of silicone oil, 500 parts of the first thermal conductive filler, 5 parts of the auxiliary agent, and 250-280 parts of the diluent; wherein,
[0075] The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent; the first thermal conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride; the diluent solvent is an alkane solvent; the auxiliary agent is one or more of Perkin catalyst, hydrogen-containing silicone oil with cross-linking effect, and silane coupling agent.
[0076] It is understandable that 100 parts of vinyl silicone resin, 500 parts of the first thermal conductive filler, and 5 parts of the auxiliary agent are preferred components, without excluding other components, or changing the corresponding components according to the thermal conductivity requirements, such as floating up and down a certain proportion according to the above components.
[0077] In a specific embodiment, the silicone oil of the impregnation slurry prepared by the first thermally conductive filler is vinyl silicone resin, and its viscosity range is 100cp-300cp at 25°C; the first thermally conductive filler is alumina, and its particle size distribution is: D50 is equal to 2μm, D100 is less than 3μm; the dilution solvent is isoparaffin, and the isoparaffin can be 260 parts; the auxiliary agent is a Perkin catalyst.
[0078] It should be noted that the first thermally conductive filler is alumina, and its particle size distribution is: D50 is equal to 2μm, and D100 is less than 3μm. That is, 50% of the alumina particles have a particle size greater than 2μm, and 50% of the particles have a particle size less than 2μm, that is, the median particle size is equal to 2μm, and the particle size of all alumina particles is less than 3μm. It should be emphasized that in addition to satisfying the above-mentioned particle size distribution, the particle size of alumina also needs to satisfy that the particle size of all particles is maintained within a range of not less than 0.5μm and not more than 5μm, and the particle size of all particles is greater than the particle size of all particles of the second thermally conductive filler. In this way, a denser stacking is achieved and the thermal conduction channel is optimized. That is, a smaller fillable gap is formed in the internal space structure of the carbon fiber gel sheet (also called carbon fiber aerogel sheet), which is conducive to the second impregnation to form a denser filling, and further form multi-directional thermal conductivity.
[0079] The viscosity of vinyl silicone resin at 25°C ranges from 100cp to 300cp (centipoises). It should be noted that the use of 100cp to 300cp low-viscosity addition-type silicone resin (vinyl silicone resin) as a reinforcing resin can reduce the viscosity of the impregnation slurry, increase the wrapping of the thermal conductive filler, and make it easier to bond and fix with the carbon fiber.
[0080] In step S210, as a specific example, the above materials are mixed, dispersed and diluted into a slurry with good fluidity. After the sintered carbon fiber gel sheet is immersed in the slurry, it is lifted up vertically, rolled with double comma rollers and the surface is flattened, and then it enters the oven to complete the cross-linking and curing of the slurry. After cooling, it is immersed in the slurry again, lifted up vertically, rolled with double comma rollers and the surface is flattened, and then it enters the oven for curing. Repeat the dipping and curing for 2-5 times (preferably 5 times in this embodiment), so that the gaps between the carbon fibers have the bonding of thermal conductive fillers and silicone resin, and a carbon fiber gel sheet with a certain strength that has been impregnated and cured is obtained. Among them, the temperature range of the oven is 80℃-125℃, and the baking time is 10-20min. In a specific embodiment, the oven curing temperature is 100℃, and the baking time is 15min.
[0081] It should be noted that the double comma roller uses two comma rollers, that is, two comma rollers are set in the vertical lifting direction after the carbon fiber gel sheet is immersed in the slurry, forming a double comma roller with an upper and lower structure. On the one hand, the first thermal conductive filler immersed in the carbon fiber gel sheet can better penetrate into the internal space structure of the carbon fiber gel sheet and form a stable structure; on the other hand, the added lower comma roller can adjust the pressing gap of the carbon fiber gel sheet, forming a good pressure while facilitating better scraping off the residual slurry, so as to obtain a carbon fiber gel sheet with smooth and slurry-free surfaces on both sides.
[0082] Table 1 Comparison of tensile strength and thermal conductivity of carbon fiber gel sheets without impregnation and curing and impregnation and curing
[0083] Thickness(mm) Tensile strength(MPa) Thermal conductivity (W / mK) Not impregnated and cured 0.1 0.012 0.02 Impregnated and cured 0.11 0.064 0.31
[0084] As shown in Table 1 above, the carbon fiber gel sheet obtained after impregnation and curing through step S100 and step S200 and the refinement step S210 has a thermal conductivity and tensile strength significantly better than the carbon fiber gel sheet that has been impregnated and cured through step S100 but not through step S200. It should be noted that the thickness of the prepared carbon fiber gel sheet will increase slightly after impregnation and curing.
[0085] In some specific embodiments, the impregnation slurry prepared from the second thermally conductive filler comprises the following steps:
[0086] The following components in parts by weight are mixed and dispersed, and then diluted with isoparaffin to form a slurry:
[0087] 100 parts of silicone oil, 400-800 parts of the second thermal conductive filler, 5 parts of the auxiliary agent, and 250-280 parts of the diluent; wherein,
[0088] The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent; the second thermally conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride; the diluent solvent is an alkane solvent; the auxiliary agent is one or more of Perkin catalyst, hydrogen-containing silicone oil with cross-linking effect, and silane coupling agent.
[0089] It should be noted that the above-mentioned 20 parts of vinyl silicone resin, 80 parts of vinyl silicone oil, and 5 parts of auxiliary agent are preferred components, and other components are not excluded, or the corresponding components can be changed according to the thermal conductivity requirements, such as floating up and down a certain proportion according to the above-mentioned components.
[0090] In a specific embodiment, the silicone oil of the impregnation slurry prepared by the second thermally conductive filler includes 20 parts of vinyl silicone resin and 80 parts of vinyl silicone oil, the viscosity of the vinyl silicone resin at 25°C is equal to 100cp, and the viscosity of the vinyl silicone oil at 25°C is equal to 5000cp; the second thermally conductive filler includes 300-500 parts of aluminum oxide and 100-300 parts of aluminum nitride; the particle size of aluminum oxide is D100 not less than 0.5μm and not more than 1μm, and the particle size of aluminum nitride is D50 equal to 1μm; the isoparaffin can be 260 parts, and the auxiliary agent is a Perkin catalyst.
[0091] It should be emphasized that the particle size of aluminum oxide is D100 not less than 0.5 μm and not more than 1 μm, the particle size of aluminum nitride is D50 equal to 1 μm, and the particle size of all particles is maintained in the range of not less than 0.5 μm and not more than 5 μm, and the particle size of all particles is smaller than the particle size of all particles of the first thermally conductive filler.
[0092] It should be noted that the second thermally conductive filler uses ultra-fine spherical alumina with a minimum particle size of 0.5μm and aluminum nitride with a median particle size of 1μm. At the same time, the carbon fiber gel sheet filled with the first thermally conductive filler in the internal space structure is calendered and the surface is flattened using a double comma roller after being immersed in the impregnation slurry prepared by the second thermally conductive filler and before cross-linking and curing. As a result, the gap between the large-particle alumina after impregnation in step S210 can be better filled to form a tight and stable structure between the large-particle filler and the small-particle filler, thereby improving the heat conduction capacity. At the same time, it is ensured that both sides of the prepared carbon fiber cloth are flat and free of slurry, which is conducive to the performance of the carbon fiber cloth and subsequent product processing.
[0093] Furthermore, alumina is easy to disperse with a high filling amount, and aluminum nitride has a higher thermal conductivity, but excessive filling will make the slurry thicker and difficult to fill deep into the internal gaps of the carbon fiber gel sheet. A specific ratio of the two (such as a 2:1 component ratio of alumina to aluminum nitride) can achieve the optimal balance between process and thermal conductivity.
[0094] The viscosity of vinyl silicone resin is equal to 100cp at 25℃, and the viscosity of vinyl silicone oil is equal to 5000cp at 25℃. It should be noted that the combination of medium-high viscosity vinyl silicone oil and low viscosity vinyl silicone resin can ensure that the thermal conductive filler is wrapped to obtain sufficient thermal conductivity, and at the same time ensure the structural strength and flexibility after curing to ensure the application of subsequent composite processes.
[0095] As another optional embodiment, the above-mentioned auxiliary agent can be a silane coupling agent, which is a long carbon chain coupling agent. Silane coupling agents with more than 16 carbon atoms are selected as auxiliary agents to improve the surface bonding between the thermal conductive filler and the carbon fiber, and provide a better bonding basis for the subsequent composite of the thermal conductive insulation layer (see step S400).
[0096] In step S220, as a specific example, the above components are mixed, dispersed and diluted into a slurry with good fluidity. The carbon fiber gel sheet that has been treated with the first impregnation and curing treatment (treated by step S210) is immersed in the slurry and then vertically lifted up and rolled with a double comma roller and the surface is flattened. After calendering and flattening, it enters the oven to complete the cross-linking and curing of the slurry. After cooling, it enters the slurry again and is vertically lifted up again and rolled with a double comma roller and the surface is flattened to enter the oven for curing. The impregnation and curing are repeated 2-5 times, so that the ultrafine alumina particles and aluminum nitride particles completely fill the gaps inside the carbon fiber, and finally a thin thermal conductive coating layer is formed on both sides of the carbon fiber layer, thereby obtaining a carbon fiber cloth with high strength, good flexibility and horizontal and vertical thermal conductivity. Among them, the temperature range of the oven is 80℃-125℃, and the baking time is 10-20min. In a specific embodiment, the oven curing temperature is 100℃ and the baking time is 15min. This carbon fiber cloth is used for the composite layer of subsequent products, and can also be used directly as a product of the present invention alone.
[0097] like Figure 4-Figure 5 As shown, by filling the first thermally conductive filler (50% of the alumina has a median particle size of 2 μm, and all the alumina particles have a particle size of less than 3 μm), an optimized thermal conductive channel is formed, and its thermal conductivity is enhanced (such as Figure 5 The solid arrow in the figure). Further, by filling the second thermally conductive filler (the particle size of aluminum oxide is D100 not less than 0.5 μm and not more than 1 μm, and the particle size of aluminum nitride is D50 equal to 1 μm) in the gap formed between the first thermally conductive filler and the unfilled internal space structure of the carbon fiber gel sheet, the gap between the large particles of aluminum oxide of the first thermally conductive filler is better filled to form a stack, thereby further improving the thermal conductivity (such as Figure 5 The obtained carbon fiber cloth has the form of large particles (first thermal conductive filler) bonded to the carbon fiber, and small particles (second thermal conductive filler) further fill the remaining gaps between the large particles and the carbon fiber to form a pile. This enables the carbon fiber cloth to achieve thermal conductivity in both horizontal and vertical directions.
[0098] In some specific embodiments, the thermally conductive insulating material is a combination of aluminum nitride and aluminum oxide with different particle sizes. In the thermally conductive insulating material, the aluminum nitride component ratio is 10%-20%.
[0099] Furthermore, the proportion of aluminum nitride is 15%, and the proportion of aluminum oxide is 85%.
[0100] In some specific embodiments, the weight proportions of vinyl silicone oil, thermal conductive insulating ingredients, and additives are as follows:
[0101] 100 parts of vinyl silicone oil, 2000 parts of thermally conductive insulating ingredients, and 2 parts of auxiliary agents. Among them, the viscosity range of vinyl silicone oil at 25°C is 500cp-2000cp. In a specific embodiment, the viscosity of vinyl silicone oil at 25°C can be preferably 1000cp; the auxiliary agent is one or more of a Perkin catalyst, a hydrogenated silicone oil with a cross-linking effect, and a silane coupling agent. In a specific embodiment, the auxiliary agent is a silane coupling agent, which is preferably a long carbon chain coupling agent. A silane coupling agent with more than 16 carbon atoms is selected as an auxiliary agent to provide a better bonding basis for the composite of the above-prepared carbon fiber layer and the thermally conductive insulating layer. It can be understood that 100 parts of vinyl silicone oil, 2000 parts of thermally conductive insulating ingredients, and 2 parts of auxiliary agents are preferred components, and other components are not excluded, or the corresponding components are changed according to the thermal conductivity requirements, such as floating up and down a certain proportion according to the above components.
[0102] In step S400, the above components are mixed into a slurry, which is compounded on at least one side of the cross-linked and cured carbon fiber cloth by scraping, spraying or calendering to form a composite layer, and then heated and cured in an oven to obtain a soft, highly compressible, insulating and highly thermally conductive insulating thermal absorbing gasket in both vertical and horizontal directions. The temperature range of the oven is 80°C-125°C, and the time is 10-20 minutes. In a specific embodiment, the oven curing temperature is 100°C, and the time is 15 minutes.
[0103] Through the above steps of "filling + insulating coating" of thermal conductive filler, a soft, highly compressible, insulating insulating thermal absorbing gasket with high thermal conductivity in both vertical and horizontal directions is formed.
[0104] It is understandable that the method can also change the overall thermal conductivity by adding different portions of thermally conductive fillers. The present invention will formulate different thicknesses according to the needs of different carbon fiber composite insulating thermally conductive absorbing gasket products. For example, a carbon fiber composite insulating thermally conductive absorbing gasket has a thickness of 2mm and adopts a BAB sandwich structure, A is a carbon fiber cloth, and B is a thermally conductive insulating gasket layer with a thermal conductivity of 6W (the thermally conductive insulating gasket layer is coated on both sides of the reinforced carbon fiber cloth, thereby forming a thermally conductive insulating layer).
[0105] Embodiment 2:
[0106] This example provides an example of comparing a carbon fiber composite insulating heat-conductive absorbing gasket prepared according to the method in the above-mentioned embodiment 1 with a common insulating heat-conductive absorbing gasket. The gasket is prepared by the preparation method described in embodiment 1, and includes a heat-absorbing and heat-conductive layer composed of carbon fiber cloth and an insulating heat-conductive layer composed of insulating heat-conductive slurry covering both sides of the carbon fiber cloth. The thickness of the carbon fiber composite insulating heat-conductive absorbing gasket is 2mm; the thickness of the heat-absorbing and heat-conductive layer (carbon fiber cloth) is 0.05mm, 0.1mm, 0.3mm, and 0.5mm, respectively. In the process of preparing the carbon fiber cloth of the above thickness, the first impregnation and curing (step S210 in embodiment 1) is performed 5 times, and the viscosity of the vinyl silicone resin is 100cp. In the second impregnation and strengthening treatment (step S220 in embodiment 1), the mass component of aluminum oxide is 400 parts, the mass component of aluminum nitride is 200 parts, and the impregnation and curing times are 4 times. In the process of preparing the thermally conductive insulating layer, the preferred thermally conductive insulating ingredient ratio is adopted, wherein the aluminum nitride component ratio is 15% (300 parts) and the aluminum oxide component ratio is 85% (1700 parts). As shown in Table 2 below, it is an example of comparing the carbon fiber composite insulating thermally conductive absorbing gasket prepared according to the method in Example 1 with the ordinary insulating thermally conductive absorbing gasket.
[0107] It can be seen from Table 2 below that the thicker the carbon fiber cloth layer is during the production of the carbon fiber composite insulating thermally conductive absorbing gasket prepared by this method, the lower the overall thermal conductivity, the smaller the density, the wider the absorbing frequency band, and the easier it is to solve the low-frequency absorption. Conversely, the thinner the carbon fiber cloth layer is, the better the insulation performance is and the lower the cost price is. No matter which thickness of carbon fiber cloth is used for composite products, compared with ordinary absorbing gaskets, low density can be achieved and the insulation performance is improved. When the thickness of the carbon fiber cloth is 0.05mm-0.1mm, its thermal conductivity is improved, and when the thickness of the carbon fiber cloth is 0.3mm-0.5mm, its absorbing frequency band is improved. Furthermore, the carbon fiber composite insulating thermally conductive absorbing gasket prepared by this method can improve the thermal conductivity, insulation, absorbing and other properties of existing insulating thermally conductive absorbing gaskets.
[0108] Table 2 Performance comparison between carbon fiber composite insulation thermal absorbing pads of different thicknesses and ordinary thermal absorbing pads
[0109]
[0110]
[0111] Embodiment 3:
[0112] This embodiment provides a specific example of the effect of different impregnation and curing times on the performance of the prepared carbon fiber cloth prepared by the steps in Example 1. Different from Example 2, the thickness of the carbon fiber cloth in this embodiment is 0.1 mm, and the number of impregnation and curing in the first impregnation and curing treatment (step S210 in Example 1) is 5 times. In the second impregnation and curing treatment (step S220 in Example 1), the number of impregnation and curing is 0 times, 2 times, 3 times, 4 times, and 5 times, respectively. The density, breakdown performance, thermal conductivity, and wave absorption performance of the prepared carbon fiber cloth were tested, and the results are shown in Table 3 below.
[0113] It can be seen from Table 3 that when the viscosity of the absorption slurry is not much different, multiple impregnations will allow the thermal conductive slurry to fully fill the internal gaps of the carbon fiber gel sheet, forming the best density, thereby improving the strength of the carbon fiber cloth while obtaining the required vertical thermal conductivity. In general, the first impregnation and curing treatment is impregnated and cured 5 times, and the second impregnation and curing treatment is impregnated and cured 4-5 times, so that a carbon fiber cloth with better performance can be obtained.
[0114] Table 3 Comparison of the effects of impregnation and curing times on the performance of carbon fiber cloth
[0115]
[0116]
[0117] Example 4: This example provides an example of preparing a carbon fiber composite insulating heat-conducting absorbing gasket using the steps in Example 1. The thickness of the carbon fiber cloth is 0.1 mm, and the total thickness of the gasket is 2 mm. In the process of preparing the carbon fiber cloth of the above thickness, the first impregnation and curing treatment (step S210 in Example 1) is performed 5 times, and the viscosity of the aluminum oxide is 500 parts and the viscosity of the vinyl silicone resin at 25°C is 100 cp. In the second impregnation and strengthening treatment (step S220 in Example 1), the mass component of aluminum oxide is 300 parts, the mass component of aluminum nitride is 100 parts, and the impregnation and curing times are 4 times. In the process of preparing the thermally conductive insulating layer, the proportion of aluminum nitride is 10% (200 parts), the proportion of aluminum oxide is 90% (1800 parts), and the viscosity of the vinyl silicone oil at 25°C is 1000 cp. After preparation, density, breakdown, thermal conductivity and wave absorption performance tests were carried out, and the corresponding density, breakdown performance, thermal conductivity and wave absorption performance test results are shown in Table 4 below. The carbon fiber composite insulating thermal conductive wave absorbing gasket prepared by this method can improve the thermal conductivity and insulation performance of the existing insulating thermal conductive wave absorbing thermal gasket.
[0118] Table 4 Performance of the carbon fiber composite insulating heat-conducting absorbing gasket prepared in this embodiment
[0119] <![CDATA[Density g / mm 3 > 3.4 Thermal conductivity W / mK 4.8 Breakdown voltage kV / mm 5.5 Absorption frequency band GHz (-5d'b) 4-20
[0120] Example 5: This example provides an example of preparing a carbon fiber composite insulating heat-conducting absorbing gasket using the steps in Example 1. The thickness of the carbon fiber cloth is 0.1 mm, and the total thickness of the gasket is 2 mm. In the process of preparing the carbon fiber cloth of the above thickness, the first impregnation and curing (step S210 in Example 1) is performed 5 times, and the viscosity of the aluminum oxide is 500 parts and the viscosity of the vinyl silicone resin at 25°C is 100 cp. In the second impregnation and strengthening treatment (step S220 in Example 1), the mass component of aluminum oxide is 500 parts, the mass component of aluminum nitride is 300 parts, and the impregnation and curing times are 4 times. In the process of preparing the thermally conductive insulating layer, the proportion of aluminum nitride is 20% (400 parts), the proportion of aluminum oxide is 80% (1600 parts), and the viscosity of the vinyl silicone oil at 25°C is 1000 cp. After preparation, density, breakdown, thermal conductivity and wave absorption performance tests were carried out, and the corresponding density, breakdown performance, thermal conductivity and wave absorption performance test results are shown in Table 5 below. The carbon fiber composite insulating thermal conductive wave absorbing gasket prepared by this method can improve the thermal conductivity and insulation performance of the existing insulating thermal conductive wave absorbing thermal gasket.
[0121] Table 5 Performance of the carbon fiber composite insulating heat-conducting absorbing gasket prepared in this embodiment
[0122] Density g / mm3 3.4 Thermal conductivity W / mK 5.5 Breakdown voltage kV / mm 5.5 Absorption frequency band GHz (-5d'b) 4-20
[0123] Example 6: This example provides an example of preparing a carbon fiber composite insulating thermally conductive absorbing gasket using the steps in Example 1. The thickness of the carbon fiber cloth is 0.1 mm, and the total thickness of the gasket is 2 mm. In the process of preparing the carbon fiber cloth of the above thickness, the first impregnation and curing (step S210 in Example 1) is performed 5 times, and the viscosity of the aluminum oxide is 500 parts and the viscosity of the vinyl silicone resin at 25°C is 100 cp. In the second impregnation and strengthening treatment (step S220 in Example 1), the mass component of aluminum oxide is 400 parts, the mass component of aluminum nitride is 200 parts, and the impregnation and curing times are 4 times. In the process of preparing the thermally conductive insulating layer, the proportion of aluminum nitride is 15% (300 parts), the proportion of aluminum oxide is 85% (1700 parts), and the viscosity of the vinyl silicone oil at 25°C is 1000 cp. After preparation, density, breakdown, thermal conductivity and wave absorption performance tests were carried out. The corresponding density, breakdown performance, thermal conductivity and wave absorption performance test results are shown in Table 6 below. The carbon fiber composite insulating thermal conductive wave absorbing gasket prepared by this method can improve the thermal conductivity, insulation and performance of the existing insulating thermal conductive wave absorbing thermal gasket.
[0124] Table 6 Performance of the carbon fiber composite insulating heat-conducting absorbing gasket prepared in this embodiment
[0125] <![CDATA[Density g / mm 3 > 3.4 Thermal conductivity W / mK 5.1 Breakdown voltage kV / mm 5.5 Absorption frequency band GHz (-5d'b) 4-20
[0126] Embodiment 7: This embodiment provides an application of a carbon fiber composite insulating heat-conductive wave-absorbing gasket. The carbon fiber composite insulating heat-conductive wave-absorbing gasket is prepared by the method in Embodiment 1. The carbon fiber composite insulating heat-conductive wave-absorbing gasket of this embodiment has excellent thermal conductivity in the horizontal and vertical directions, and thus can be used as an insulation, heat conduction, and wave absorption application between the components of the heat source and the heat sink. It can be widely used in electronic equipment, smart wearable devices, communication equipment and other fields to achieve insulation, heat conduction, and wave absorption between the components of the heat source and the heat sink.
[0127] It should be understood that, although the steps in the flowcharts involved in the above embodiments are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear explanation in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a part of the steps in the flow involved in the above embodiments can include multiple steps or multiple stages, and these steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a part of the steps or stages in other steps.
[0128] The above description is only a preferred embodiment of the present invention. It is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket, characterized in that: The steps include: The polyimide film of a specified thickness is sintered and carbonized at a high temperature to form a carbon fiber gel sheet with an internal space structure; The carbon fiber gel sheet is immersed in an impregnation slurry prepared by a first thermally conductive filler, and then the slurry is cross-linked and cured. After the cross-linking and curing, the carbon fiber gel sheet is immersed in an impregnation slurry prepared by a second thermally conductive filler, and then the slurry is cross-linked and cured to obtain a carbon fiber cloth filled with thermally conductive fillers of different particle sizes in the internal space structure; wherein the particle size of the first thermally conductive filler is larger than the particle size of the second thermally conductive filler, and the particle size of the first thermally conductive filler and the particle size of the second thermally conductive filler are both not less than 0.5 μm and not more than 5 μm; Aluminum oxide and aluminum nitride are mixed in a certain proportion to form a thermally conductive and insulating ingredient, and components including vinyl silicone oil, thermally conductive and insulating ingredients, and additives are mixed in parts by weight to form a slurry with thermally conductive and insulating properties; The mixed slurry is compounded on one side or both sides of the carbon fiber cloth and heated and cured to obtain a carbon fiber composite insulating heat-conducting wave-absorbing gasket.
2. The method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 1, characterized in that: The weight proportions of vinyl silicone oil, thermal conductive insulating ingredients, and additives are as follows: 100 parts of vinyl silicone oil, 2000 parts of thermal conductive insulating ingredients, and 2 parts of additives.
3. The method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 2, characterized in that: The viscosity of the vinyl silicone oil at 25° C. is in the range of 500 cp to 2000 cp; The auxiliary agent is one or more of a Perkin catalyst, a hydrogen-containing silicone oil having a cross-linking effect, and a silane coupling agent.
4. The method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 1, characterized in that: Obtaining a carbon fiber cloth filled with thermal conductive fillers of different particle sizes in the internal space structure comprises the following steps: The carbon fiber gel sheet is immersed in the impregnation slurry prepared by the first thermal conductive filler for impregnation, and after impregnation, it is calendered by a double comma roller and the surface is flattened, and after calendering and surface flattening, the slurry is cross-linked and cured, and after curing, the impregnation and curing steps are repeated several times to obtain a carbon fiber gel sheet filled with the first thermal conductive filler in the internal space structure; The impregnated and cured carbon fiber gel sheet is immersed in the impregnation slurry prepared by the second thermally conductive filler for impregnation, and after impregnation, it is calendered by a double comma roller and the surface is flattened. After calendering and surface flattening, the slurry is cross-linked and cured. After curing, this step of impregnation and curing is repeated several times to obtain a carbon fiber cloth filled with the second thermally conductive filler in the gap formed between the first thermally conductive filler and the unfilled internal space structure.
5. A method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to any one of claims 1 to 4, characterized in that: The impregnation slurry prepared from the first thermally conductive filler comprises the following steps: Mix and disperse the following components by weight and dilute them into a slurry: 100 parts of silicone oil, 500 parts of the first thermal conductive filler, 5 parts of the auxiliary agent, and 250-280 parts of the diluent; wherein, The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent; The first thermally conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride; The dilution solvent is an alkane solvent; The auxiliary agent is one or more of a Perkin catalyst, a hydrogen-containing silicone oil having a cross-linking effect, and a silane coupling agent.
6. The method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 5, characterized in that: The silicone oil of the impregnation slurry prepared from the first thermally conductive filler is a vinyl silicone resin, and its viscosity ranges from 100cp to 300cp at 25°C; The first thermally conductive filler is aluminum oxide, and its particle size distribution is: D50 is equal to 2 μm, and D100 is less than 3 μm.
7. A method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to any one of claims 1 to 4, characterized in that: The impregnation slurry prepared from the second thermally conductive filler comprises the following steps: Mix and disperse the following components by weight and dilute them into a slurry: 100 parts of silicone oil, 400-800 parts of the second thermal conductive filler, 5 parts of the auxiliary agent, and 250-280 parts of the diluent; wherein, The silicone oil is one or more of vinyl silicone oil, vinyl silicone resin, hydrogen-containing silicone oil, and silane coupling agent; The second thermally conductive filler is one or more of aluminum oxide, aluminum nitride, and boron nitride; The dilution solvent is an alkane solvent; The auxiliary agent is one or more of a Perkin catalyst, a hydrogen-containing silicone oil having a cross-linking effect, and a silane coupling agent.
8. The method for preparing a carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 7, characterized in that: The silicone oil of the impregnation slurry prepared by the second thermally conductive filler includes 20 parts of vinyl silicone resin and 80 parts of vinyl silicone oil, wherein the viscosity of the vinyl silicone resin at 25° C. is equal to 100 cp, and the viscosity of the vinyl silicone oil at 25° C. is equal to 5000 cp; The second thermally conductive filler comprises 300-500 parts of aluminum oxide and 100-300 parts of aluminum nitride; The particle size of the aluminum oxide is D100 not less than 0.5 μm and not more than 1 μm, and the particle size of the aluminum nitride is D50 equal to 1 μm.
9. A carbon fiber composite insulating heat-conducting wave-absorbing gasket, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8, comprising a wave absorbing heat conducting layer composed of carbon fiber cloth, and an insulating heat conducting layer composed of an insulating heat conducting slurry covering one or both sides of the carbon fiber cloth; The thickness of the wave absorbing and heat conducting layer is in the range of 0.05 mm to 0.5 mm.
10. An application of the carbon fiber composite insulating heat-conducting wave-absorbing gasket according to claim 9, characterized in that: It is used for insulation, heat conduction and wave absorption between heat source components and heat sink.
Citation Information
Cited By
High-thermal-conductivity wave-absorbing carbon fiber heat-conducting gasket and preparation method thereof
CN122445192A